A Test of Income Smoothing Using Pseudo Fiscal Years - Black, Dirk E.; Pierce, Spencer R.; Thomas, Wayne B. (Management Science, 2022)
The purpose of our study is to further understand managerial incentives that affect the volatility of reported earnings. Prior research suggests that the volatility of fourth-quarter earnings may be affected by the integral approach to accounting (i.e., “settling up” of accrual estimation errors in the first three quarters of the fiscal year) or earnings management to meet certain reporting objectives (e.g., analyst forecasts). We suggest that another factor affecting fourth-quarter earnings is managers’ intentional smoothing of fiscal-year earnings. For each firm, we create pseudo-year earnings using four consecutive quarters other than the four quarters of the reported fiscal year. We then compare the earnings volatility of pseudo years to the earnings volatility of the firm’s own reported fiscal year. We find evidence consistent with fourth-quarter accruals reflecting managerial incentives to smooth fiscal-year earnings. This conclusion is validated by several cross-sectional tests, the pattern in quarterly cash flows and accruals, and several robustness tests. Overall, we contribute to the literature exploring alternative explanations for the differential volatility of fiscal-year and fourth-quarter earnings. This paper was accepted by Brian Bushee, accounting.